2007
DOI: 10.1073/pnas.0701681104
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of PrBP/δ impedes transport of GRK1 and PDE6 catalytic subunits to photoreceptor outer segments

Abstract: The mouse Pde6d gene encodes a ubiquitous prenyl binding protein, termed PrBP/␦, of largely unknown physiological function. PrBP/␦ was originally identified as a putative rod cGMP phosphodiesterase (PDE6) subunit in the retina, where it is relatively abundant. To investigate the consequences of Pde6d deletion in retina, we generated a Pde6d ؊/؊ mouse by targeted recombination. Although manifesting reduced body weight, the Pde6d ؊/؊ mouse was viable and fertile and its retina developed normally. Immunocytochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
184
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(195 citation statements)
references
References 35 publications
7
184
0
Order By: Relevance
“…Previous studies have shown that KRAS KO in mice is lethal (41,42) but that PDEδ KO is not (43). This difference may be because PDEδ helps in the localization of KRAS4b, not of KRAS4a, and therefore, only affects one isoform of KRAS.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that KRAS KO in mice is lethal (41,42) but that PDEδ KO is not (43). This difference may be because PDEδ helps in the localization of KRAS4b, not of KRAS4a, and therefore, only affects one isoform of KRAS.…”
Section: Discussionmentioning
confidence: 85%
“…We show that PDEd is bound to one of the highest conserved surface patches where we cannot locate any of the patient mutations. This might indicate that the loss of this interaction is not tolerated [22].…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal functions of mammalian PDE6␦ have been previously studied in rods and cones, where it regulates transport of phosphodiesterase PDE6, rhodopsin kinase, and G t␣ -all prenylated proteins-to the outer segment of these ciliated neurons (Li et al, 1998;Norton et al, 2005;Zhang et al, 2007;Luo et al, 2008). Like cone and rod photoreceptors, BAG has a ciliated dendritic ending, but URX is a nonciliated neuron (Ward et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies showed that it is a prenyl binding protein (PrBP) that can extract prenylated proteins such as small lipidated GTPases (e.g., Ras) from membranes, sequestering them in the cytoplasm, and facilitating their traffic to different membrane compartments . Mice lacking PDE6␦ are small but viable; they exhibit progressive cone-rod dystrophy and defective localization of prenylated rhodopsin kinase (GRK1) and PDE6 catalytic subunits to rod outer segments (Zhang et al, 2007).…”
Section: Elegans Pde6␦/prbp Prenyl Binding Protein Is Required Formentioning
confidence: 99%